Promoting Feliz Guest House Surabaya by Emphasizing Its Unique Selling Points in Its Marketing Booklet - Gitta Sanjaya (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
Feliz Guest House is a 2-star hotel which located at Jl. Raya Kendangsari No. 80, Surabaya. FGH is a guesthouse with a concept of a mini hotel. Their main competitors are Home Guest House, SepuluhEnam Homestay, and Savira Guest House. The main problem that FGH is facing is the decline of occupancy rate in the past three years. To solve the problem, I think FGH needs a marketing booklet that can help them promote and emphasize its unique selling points. A marketing booklet will be a good solution to the problem is because FGH can effectively promote the business to potential customers. By knowing the purpose of the company and its uniqueness, it will create a positive image on the customers’ mind. The benefit that the company will get is that they can use it to promote their company and its products to the new customers in order to increase the sales. Keywords: Promotion, Promotional Tool, Unique Selling Points, Marketing Booklet.